Reduction of Friction and Adhesion in Copper and Brass Extrusion by Application of Boron Containing Surface Modifications - The Minerals Metals & Materials Society (TMS 2023 152nd Annual Meeting & Exhibition Supplemental Proceedings, 2023)
Due to extensive abrasion and adhesion, tools for copper and brass extrusionCopper and brass extrusion are subject to considerable wear. In the present study, the effect of boron containing surface modificationsBoron containing surface modificationson friction and adhesionFriction and adhesion was investigated by means of a high-temperature, high-speed friction test for extrusion. A Ti-Si-B-C-N nanocomposite coating and a boridic diffusion layer were applied to hot work toolTool wear steel 1.2367 and nickel-based alloy 2.4668, respectively. Using billets made of copper alloy CW024A and brass alloy CW724R, the friction tests were performed at high temperatures and normal pressures typical of the extrusion process. The evaluation of the obtained test data indicates a significant influence of the Ti-Si-B-C-N nanocomposite coating on the friction and adhesion behavior of the investigated material pairings. While friction and adhesionFriction and adhesion are greatly reduced for the Ti-Si-B-C-N coating, the effect of the boridic diffusion layer is substantially less.